Respiration and rapid eye movement (REM) sleep substructure: short versus long episodes - Hammer, Maximilian; Jung, Felix; Brankačk, Jurij; Yanovsky, Yevgenij; Tort, Adriano B. L.; Draguhn, Andreas (Journal of sleep research, 2023)
Rapid eye movement (REM) sleep in rodents is defined by the presence of theta rhythm in the absence of movement. The amplitude and frequency of theta oscillations have been used to distinguish between tonic and phasic REM sleep. However, tonic REM sleep has not been further subdivided, although characteristics of network oscillations such as cross-frequency coupling between theta and gamma vary within this sub-state. Recently, it has been shown that theta-gamma coupling depends on an optimal breathing rate of 5 Hz. The frequency of breathing varies strongly throughout REM sleep, and the duration of single REM sleep episodes ranges from several seconds to minutes, whereby short episodes predominate. Here we studied the relation between breathing frequency, accelerometer activity, and the length of REM sleep periods. We found that small movements detected with three-dimensional accelerometry positively correlate with breathing rate. Interestingly, breathing is slow in short REM sleep episodes, while faster respiration regimes exclusively occur after a certain delay in longer REM sleep episodes. Thus, merging REM sleep episodes of different lengths will result in a predominance of slow respiration due to the higher occurrence of short REM sleep periods. Moreover, our results reveal that not only do phasic REM sleep epochs predominantly occur during long REM sleep episodes, but that the long episodes also have faster theta and higher gamma activity. These observations suggest that REM sleep can be further divided from a physiological point of view depending on its duration. Higher levels of arousal during REM sleep, indicated by higher breathing rates, can only be captured in long REM sleep episodes.